Population pharmacokinetic modelling and simulation of 5-fluorouracil incorporating a circadian rhythm in rats. (2nd July 2016) - Kobuchi, Shinji; Ito, Yukako; Nakano, Yuya; Sakaeda, Toshiyuki
Abstract: 1. The aim of this study was to develop a population pharmacokinetic (PK) model for 5-fluorouracil (5-FU) and perform simulations to identify the circadian rhythm of the PK of 5-FU and the degree of circadian effects on the 5-FU plasma concentrations. 2. 5-FU plasma concentrations in rats following administration of 5-FU at varying time points throughout the day were obtained and used to develop the population PK model incorporating a circadian rhythm. The Cosinor method was used to describe the circadian variation of 5-FU clearance. 3. Our population PK model could successfully characterize the 5-FU disposition and provide reliable PK parameter estimates. The mesor, amplitude and acrophase of Cosinor model were estimated as 1.93 L/h/kg, 0.10 L/h/kg and 2.02 h, respectively. The peak clearance levels were estimated at ∼2 Hours After Light Onset (HALO) and the trough levels at ∼14 HALO. The plasma concentration–time profile of 5-FU after continuous infusion of 5-FU in rats successfully simulated the circadian variation of steady-state plasma concentrations. 4. The population PK model with individual 5-FU plasma concentrations, dose levels and sampling time points could be valuable for estimating area under the curve (AUC) levels and determining individual 5-FU dose management.